Kekuatan Pembuktian Akta Dibawah Tangan yang Disahkan oleh Notaris pada Perkara Perdata (Studi Kasus Perkara Nomor 75/Pdt.G/2020/PN Pdg) - Rinaldi Sarza; Ismansyah Ismansyah; Azmi Fendri (LPPM Universitas Ekasakti Padang, 2023)
This study aims to find out and analyze how the power of underhanded deeds legalized by a notary as evidence in the trial process at court in civil cases, to find out and analyze the judge's consideration of civil case decisions, and to find out and analyze the notary's responsibility for the deed has been legalized in the Civil Code. The research method in this research is the normative research method. Normative legal research is legal research carried out by examining library materials or secondary data. The results of this study, want to show how the power of underhanded deeds legalized by a notary in civil cases, basically the strength of proof of underhanded deeds legalized by a notary the power of proof cannot be equated with an authentic deed, underhanded deed legalized by a notary if denied the power changes as proof of the beginning of writing.